Chemical reactivity on gas-phase metal clusters driven by blackbody infrared radiation - Parry, I; Kartouzian, A; Hamilton, S; Balaj, O; Beyer, M; Beyer, M; Mackenzie, S (Wiley-VCH, 2015)
We report the observation of chemical reactions in gas-phase Rhn(N2O)m + complexes driven by absorption of blackbody radiation. The experiments are performed under collision-free conditions in a Fourier transform ion cyclotron resonance mass spectrometer. Mid-infrared absorption by the molecularly adsorbed N2O moieties promotes a small fraction of the cluster distribution sufficiently to drive the N2O decomposition reaction, leading to the production of cluster oxides and the release of molecular nitrogen. N2O decomposition competes with molecular desorption and the branching ratios for the two processes show marked size effects, reflecting variations in the relative barriers. The rate of decay is shown to scale approximately linearly with the number of infrared chromophores. The experimental findings are interpreted in terms of calculated infrared absorption rates assuming a sudden-death limit.